Polymorphisms of candidate genes determining the clinical and hemostasiological characteristics of endocarditis of various etiology - Y. S. Bakhareva; V. N. Maksimov; A. A. Ivanova; N. N. Chapaeva; S. V. Aidagulova; M. I. Voevoda (Бюллетень сибирской медицины, 2022)
Aim. To investigate polymorphisms of 18 genes as possible molecular genetic markers of predisposition or resistance to development of non-infective (NE) or infective endocarditis (IE).Materials and methods. The study encompassed 81 patients with NE and 94 patients with IE. The control group included 225 conditionally healthy people. Polymorphisms of 18 genes were tested using polymerase chain reaction (PCR).Results. For the first time, a statistically significant relationship was identified between gene polymorphisms and valvular vegetations: for genes in the hemostatic system – rs6025 (1691 G > A) of the F5 gene (AG genotype), rs1126643 (807 C > T) of the ITGA2 gene (TT genotype); for folate pathway genes – rs1805087 (2756 A > G) of the MTR gene (AG genotype) and rs11697325 (–8202 A/G) of the MMP9 gene (AA genotype) and rs2476601 (C1858T) of the PTPN22 gene (TT genotype). The protective effect of gene polymorphisms was revealed: for the NOS3 gene (4b / 4b genotype) and G (–572) C of the IL6 gene (CC genotype). For two polymorphisms, an association with thromboembolic complications in NE was revealed: rs1126643 (807 C > T) of the ITGA2 gene and rs1799889 (–675 5G > 4G) of the PAI (SERPINE1) gene. In IE, such an association was detected for the polymorphism rs11697325 (–8202 A/G) of the MMP-9 gene.Conclusion. The polymorphisms of candidate genes were revealed, that are associated with the clinical and hemostasiological characteristics of IE and NE. In NE, for the first time, the association with thromboembolic complications was identified for two polymorphisms: rs1126643 (807 C > T) of the ITGA2 gene and rs1799889 (– 675 5G > 4G) of the PAI-1 (SERPINE1) gene. In IE, such a relationship was detected for one polymorphism – rs11697325 (8202 A/G) of the MMP-9 gene.